“User Generated Reviews and Business Promotions” - Ravikumar, J.S.; T. , Narayana Reddy; Mohammad Ghouse, Syed (International Journal of Psychosocial Rehabilitation, 2020)
User-generated reviews are a significant motivating force overdue, specifically the foremost websites, like Amazon, Facebook, and Trip Advisor. The user-generated reviews are nothing but ratings and reviews. These ratings & reviews have been presented to influence buying decisions and quantity, together in the perspective of goods and services. User-generated reviews are a unique way to advertise how your brand stinks. Besides, product promotion joined with UGR is an opportunity for online commercials to associate with customers and yield profits. With the constant growth of social media and Google’s durable process, quality reviews of customers will play an essential role in the actions of virtually all companies seeking to stimulate the web as an efficient marketing and communications network. By analyzing the reviews, some companies make a strategy to promote their product from the reviews of the product, which are online generated. If the product from a brand gets an extensive response, the other products may not get more sales. So the company tends to stop the existing products and plan an effective promotion for the unpopular products by comparing issues in both products that got more sales and fewer sales. In this research, we propose about how the user-generated reviews are impacted on the promotion of any products. The analysis of issues from the user-generated reviews is considered for further development.